2(y+3)=4(y+5)

Simple and best practice solution for 2(y+3)=4(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y+3)=4(y+5) equation:


Simplifying
2(y + 3) = 4(y + 5)

Reorder the terms:
2(3 + y) = 4(y + 5)
(3 * 2 + y * 2) = 4(y + 5)
(6 + 2y) = 4(y + 5)

Reorder the terms:
6 + 2y = 4(5 + y)
6 + 2y = (5 * 4 + y * 4)
6 + 2y = (20 + 4y)

Solving
6 + 2y = 20 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
6 + 2y + -4y = 20 + 4y + -4y

Combine like terms: 2y + -4y = -2y
6 + -2y = 20 + 4y + -4y

Combine like terms: 4y + -4y = 0
6 + -2y = 20 + 0
6 + -2y = 20

Add '-6' to each side of the equation.
6 + -6 + -2y = 20 + -6

Combine like terms: 6 + -6 = 0
0 + -2y = 20 + -6
-2y = 20 + -6

Combine like terms: 20 + -6 = 14
-2y = 14

Divide each side by '-2'.
y = -7

Simplifying
y = -7

See similar equations:

| -20g-20=-18g+16 | | 2x-1+7x=5 | | -3s+16=12s-14-18s | | 2x+5x-9=47 | | 3-2e=8-x | | 8x+3y+7y-2x= | | 21.64=4g+3.56 | | -18-19v=-16v | | -4x-3=12x-35 | | -8(x-7)=-48 | | -4u-7=4+7u | | 8+b=4 | | 6+7(x-7)=-5 | | -9(x-1)=-63 | | 7j-2=6j | | 29+7x=-4(7-7x)-6 | | 3=w*3-16 | | 7+6p=10p-9 | | -4(r+7)=-45 | | 11.72*x=16.6424 | | 6-k+2k=10-3k | | -q+9=2q | | 29+7x=-4(7-7x) | | 5x+11y+3=0 | | 10-d=-10+3d | | 4x+3y-2z=5 | | 6(x-1)=13 | | 3b=4b+6 | | 2x-30+x-10=180 | | 18+2.50h=11+3.75h | | -2f+6=-f | | 2y=-3y-10 |

Equations solver categories